Development and Validation of a Method for the Detection and Quantification of Antidepressants and Antipsychotics in Bone Samples by GC–MS. Issue 9 (10th November 2020) - Laudani, Antonino; Sangregorio, Deborah; Zuccarello, Pietro; Licciardello, Teresa; Grasso, Stephanie; Romano, Guido; Barbera, Nunziata
Abstract: Bone marrow is the tissue contained inside the bones and can be considered one of the potential alternative tissues in forensic toxicology. This matrix could be particularly useful in those cases where the routine sample is not available due to an advanced state of decomposition or skeletonization of the corpse. The aim of this study was to develop, validate and apply an analytical method of extraction and analysis of different antidepressants and antipsychotics, commonly used in therapy, from spiked pig ribs. Pig ribs, each of 5 g and 5 cm long, were spiked at three concentration levels (100, 200 and 500 ng/g). For each concentration, 10 pig ribs were prepared. The method involves the leaching by ethanol at different pHs of nine drugs from the inside of ribs, in particular from the bone marrow, without the fragmentation of bone tissue. Following a liquid–liquid purification and extraction, analysis was performed by gas chromatography coupled with mass spectrometry in selected ion monitoring mode. For method validation was assessed linearity, sensitivity, precision and accuracy, matrix interferences and, finally, carryover. Analytical method performance was acceptable respect to acceptance criteria for validation. No matrix interferences were detected; for this reason, it is possible to affirm that this method has a good selectivity. Moreover, the method was not affected by carryover. Considering that the study conducted on pig ribs has given encouraging results, it can be assumed that this method can be used in forensic toxicological protocols (human autopsy cases) as alternative to classic procedures.